Beyond words: Pragmatic inference in behavioral variant of frontotemporal degeneration. (August 2015) - Spotorno, Nicola; McMillan, Corey T.; Rascovsky, Katya; Irwin, David J.; Clark, Robin; Grossman, Murray
Abstract: When the message of a speaker goes beyond the literal or logical meaning of the sentences used, a pragmatic inference is required to understand the complete meaning of an utterance. Here we study one example of pragmatic inference, called scalar implicature. Such an inference is required when a weaker term "some" is used in a sentence like "Some of the students passed the exam" because the speaker presumably had a reason not to use a stronger term like "all". We investigated the comprehension of scalar implicatures in a group of 17 non-aphasic patients with behavioral variant frontotemporal degeneration (bvFTD) in order to test the contribution of non-linguistic decision-making ability and the role of prefrontal cortex in supporting the computation of pragmatic inferences. The results of two experiments point to a deficit in producing alternative interpretations beyond a logical reading. bvFTD patients thus prefer the narrowly literal or logical interpretation of a scalar term when they must generate a possible alternative interpretation by themselves, but patients prefer a pragmatic reading when offered a choice between the logical and the pragmatic interpretation of the same sentence. An imaging analysis links bvFTD patients' spontaneous tendency toward a narrowly logical interpretation with atrophy in ventromedial prefrontal cortex. Our findings are consistent with the pragmatic tolerance hypothesis, which proposes that difficulty generating alternative interpretations of an utterance, rather than a frank inability to compute an inference, affects the comprehension of a scalar term. Highlights: bvFTD patients prefer the logical interpretation of a scalar term. bvFTD patients do not generate possible alternative interpretation by themselves. Patients' tendency toward a logical reading correlates with GM atrophy in vmPFC. bvFTD patients prefer a pragmatic reading when they have the choice.